2008
DOI: 10.1093/jmedent/45.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus Transmission by Culex nigripalpus in Florida, 2005

Abstract: Understanding the transmission patterns of West Nile and St. Louis encephalitis viruses (family Flaviviridae, genus Flavivirus, WNV and SLEV) could result in an increased ability to predict transmission risk to humans. To examine transmission patterns between vector and host, we trapped mosquitoes in three Florida counties from June to November 2005 by using chicken-baited lard can mosquito traps. These traps were used to monitor for presence of WNV and SLEV in mosquitoes and subsequent transmission of these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
3
29
0
2
Order By: Relevance
“…nigripalpus collected in chicken-baited lard can traps placed at three widely dispersed sites in Florida. 41 This study also noted a low rate of WNV transmission to the chickens restrained within the traps, despite seven of eight virus-positive pools containing only blooded females, a finding that corroborates previous work. 17 Vitek and others 41 speculate that the lack of virus dissemination within the infected mosquitoes may be responsible for the low transmission rate, but their experimental protocol did not allow them to test this idea.…”
Section: Ecology Of West Nile Virus Vectors In Louisianasupporting
confidence: 90%
See 2 more Smart Citations
“…nigripalpus collected in chicken-baited lard can traps placed at three widely dispersed sites in Florida. 41 This study also noted a low rate of WNV transmission to the chickens restrained within the traps, despite seven of eight virus-positive pools containing only blooded females, a finding that corroborates previous work. 17 Vitek and others 41 speculate that the lack of virus dissemination within the infected mosquitoes may be responsible for the low transmission rate, but their experimental protocol did not allow them to test this idea.…”
Section: Ecology Of West Nile Virus Vectors In Louisianasupporting
confidence: 90%
“…41 This study also noted a low rate of WNV transmission to the chickens restrained within the traps, despite seven of eight virus-positive pools containing only blooded females, a finding that corroborates previous work. 17 Vitek and others 41 speculate that the lack of virus dissemination within the infected mosquitoes may be responsible for the low transmission rate, but their experimental protocol did not allow them to test this idea. 41 In southern Florida, onset of human cases and the appearance of anti-WNV antibodies in sentinel chickens are temporally and spatially associated with prior cycles of drought and moisture in a manner similar to that seen with SLEV, thus providing strong evidence that Cx.…”
Section: Ecology Of West Nile Virus Vectors In Louisianasupporting
confidence: 90%
See 1 more Smart Citation
“…nigripalpus showed that transmission is low in relation to estimated infection rates, 38,39 and many factors that we studied here were considered to explain this occurrence. These field studies support the idea that incorporation of information on the mosquito population (age structure, abundance and estimated infection rate), virus (strain, species-specific dissemination rates), and the environment (temperature) are necessary to make assessments of the risk of virus transmission.…”
Section: Discussionmentioning
confidence: 81%
“…In that way, one would have an estimate of mosquito infection paired with a measure of transmission. 38,39 However, these methods are seldom feasible, practical, or affordable for long-term surveillance programs.…”
Section: Discussionmentioning
confidence: 99%